Ethmoid malformation associated with pediatric nasal polyposis and allergic fungal sinusitis - Hanson, Cameron G. (J Surg Case Rep, 2017)
A 17-year-old female with allergic fungal sinusitis and nasal polyposis presented with epistaxis in the emergency room. On examination, right-sided proptosis and irregular nasal obstruction were observed in the right nasal cavity. CT imaging revealed massive right-sided polyposis and significant ipsilateral malformation with boney architecture preservation of the ethmoidal labyrinth and lamina papyracea. The patient was treated surgically with symptomatic improvement. These findings indicate a unique malformation of the ethmoid while the patient was in development. To the authors’ knowledge, this anatomical malformation has not been previously described in the literature. Physicians should implement diagnostic procedures early if nasal polyposis and allergic fungal sinusitis is suspected in pediatric patients, especially with periocular involvement, to mitigate the risk of boney malformations of the sinuses.